Genome-wide CRISPR Screening Reveals Pyrimidine Metabolic Reprogramming in 5-FU Chronochemotherapy of Colorectal Cancer - Niu, Ya; Fan, Xinyi; Wang, Yaping; Lin, Jiaxin; Hua, Luchun; Li, Xiaobo; Qian, Ruizhe; Lu, Chao (Frontiers in Oncology, 2022)
Objective: Disruption of the circadian rhythm is associated with cancer occurrence, response to chemotherapy, and poor prognosis. Thus, using internal clock-based chronotherapy to optimize the administration time may improve the therapeutic effects of anticancer drugs while reducing the side effects. Chronotherapy with 5-fluorouracil (5-FU) has been observed in colorectal cancer (CRC) for a long time, but its effect is under controversial and the mechanism remains unclear. Methods: Genome-wide clustered regularly interspaced short palindromic repeats (CRISPR) screening and RNA-sequencing were combined to identify the potential genes or pathways involved in 5-FU chronochemotherapy. Genetic deletion or overexpression of pyrimidine metabolic pathway genes were conducted to examine cellular viability with or without 5-FU via flow cytometry. Western blotting, qPCR, chromatin immunoprecipitation, gain-of-function and loss-of-function assays of several CRC cell lines in vitro and in vivo were used to elaborate and validate the mechanism of 5-FU chronotherapeutic effects. Results: Chronochemotherapeutic effects of 5-FU on CRC in vivo were verified. Furthermore, 5-FU chronochemotherapy related genes such as UPP2, UCK2 and UMPS in the pyrimidine metabolic pathway were identified. Disturbance in these genes, especially UMPS, perturbs 5-FU treatment outcomes in CRC cells. Mechanistically, the core circadian gene, brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein-1 (BMAL1), extensively regulate gene expression in pyrimidine metabolic pathway by binding to E-box element in the promoter region of key genes such as UMPS and perturb their enzymatic activities, thereby maintain diurnal efficacy of 5-FU in CRC cells. Conclusion: This study uncovered a new mechanism by which a core circadian gene BMAL1 increases the effectiveness of 5-FU by enhancing the expression and enzymatic activities of key genes in the pyrimidine metabolic pathway in CRC cells. The findings suggest a novel strategy for CRC chemotherapy by targeting chrono-modulated genes of the 5-FU metabolic pathway.